The Relationship Between Family Support And Self-Motivation And Medication Adherence In Hypertensive Patients At The Pallangga Community Health Center In Gowa Regency - Deliaty Bagenda Ali; Iismayanti Iismayanti; Nurul Mutmainnah (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension is a global health problem with an increasing number of sufferers. The success of hypertension management is largely determined by patient compliance in taking medication, but noncompliance remains a common obstacle. This condition leads to suboptimal blood pressure control and increases the risk of cardiovascular complications. This study aims to determine whether there is a significant relationship between family support and self-motivation on medication adherence in hypertensive patients. This study is a quantitative study with a cross-sectional approach. The sample in this study consisted of 67 respondents, and the study was conducted at the Pallangga Community Health Center. Data collection was carried out using questionnaires on family support, self-motivation, and medication adherence. After conducting a statistical test using the Chi-Square test, the results showed that there was a significant relationship between family support and medication adherence in hypertensive patients at the Pallangga Community Health Center in Gowa Regency, with a p-value of 0.014 (< 0.05). There was also a significant relationship between self-motivation and medication adherence among hypertensive patients at the Pallangga Community Health Center in Gowa Regency, with a p-value of 0.023 (< 0.05). Family support and self-motivation are significantly related to medication adherence among hypertensive patients at the Pallangga Community Health Center in Gowa Regency. Adequate family support and high self-motivation have been proven to increase patient consistency in undergoing treatment. Thus, these two factors need to be considered in efforts to improve adherence to hypertension treatment.